The profession of dietetics - Canter, Deborah D.; DeYoung-Daniels, Rebecca (Jones & Bartlett Learning, 2021)
"The Profession of Dietetics offers students a complete toolbox of resources for beginning a career in nutrition and dietetics. Using a student-centered approach, this text enables readers to easily navigate the highly competitive and often complex path to personal and professional success in the field. It features a comprehensive history of the profession, a thorough examination of credentialing and education requirements, and an analysis of the profession's future"--